Does a single session of reading literary fiction prime enhanced mentalising performance? Four replication experiments of Kidd and Castano (2013). Issue 1 (2nd January 2018) - Samur, Dalya; Tops, Mattie; Koole, Sander L.
ABSTRACT: Prior experiments indicated that reading literary fiction improves mentalising performance relative to reading popular fiction, non-fiction, or not reading. However, the experiments had relatively small sample sizes and hence low statistical power. To address this limitation, the present authors conducted four high-powered replication experiments (combined N  = 1006) testing the causal impact of reading literary fiction on mentalising. Relative to the original research, the present experiments used the same literary texts in the reading manipulation; the same mentalising task; and the same kind of participant samples. Moreover, one experiment was pre-registered as a direct replication. In none of the experiments did reading literary fiction have any effect on mentalising relative to control conditions. The results replicate earlier findings that familiarity with fiction is positively correlated with mentalising. Taken together, the present findings call into question whether a single session of reading fiction leads to immediate improvements in mentalising.